Transnational legal orders - Halliday, Terence C. (Terence Charles); Shaffer, Gregory C., 1958- (New York : Cambridge University Press, 2015)
"This book offers an empirically grounded theory that reframes the study of law and society from a predominantly national context, which dichotomizes the study of international law and national compliance into a dynamic perspective that places national, international, and transnational lawmaking and practice within a coherent single frame. By presenting and elaborating on a new concept, transnational legal orders it offers an original approach to the emergence of legal orders beyond nation-states. It shows how they originate, where they compete and cooperate, and how they settle on institutions that legally order fundamental economic and social behaviors that transcend national borders. This original theory is applied and developed by distinguished scholars from North America and Europe in business law, regulatory law and human rights"--
7. Institutionalization and its consequences: the TLO(s) for food safety Tim Büthe; 8. Climate change: Transnational Legal Order or Disorder? Daniel Bodansky; Part III. Transnational Legal Orders and Human Rights Law: 9. Pharmaceutical patents and the human right to health: the contested evolution of the transnational legal order on access to medicines Laurence Helfer; 10. 'Rule of law' as transnational legal order Jothie Rajah; 11. Firming up soft law: the impact of indicators on transnational human rights legal orders Sally Merry; 12. Framing for a New Transnational legal order: the case of human trafficking Paulette Lloyd and Beth Simmons; 13. The justice paradox?: Transnational legal orders and accountability for past human rights violations Leigh Payne; 14. Researching transnational legal orders Terence Halliday and Gregory Shaffer.
Includes bibliographical references and index.
Includes bibliographical references and index.
Keywords: Rule of law; Law -- International unification; International trade; Foreign trade regulation; Bankruptcy -- International cooperation; LAW / General